A CU Split Early Termination Algorithm Based KNN for 360-Degree Video - Liu, Zhi; Song, Peiran; Zhang, Mengmeng (DCC (Los Alamitos, Calif.), 2019)
360-degree video has been developed rapidly and widely used in recent years.360Lib is a test platform (software) for JVET panoramic video, hosted by Subversion code. The 360Lib in this article is integrated into the HM.At this stage, coding 360 degrees video needs to convert video according to ERP, EAP, CMP and other formats, then encode with HEVC, and then reverse transform to 360 degree video.Since 360lib just transforms the projection format, it still uses HEVC to code, and does not use the 360-degree video's characteristics. Based on the characteristics of 360lib, this paper proposes a A CU Split Early Termination Algorithm. Experimental results show that the proposed fast algorithm provides an average time reduction rate of 32% compared to the reference HM-16.16+360lib4.0, with only 1.3% BD-rate increase.